Molecular mechanism of VE-cadherin in regulating endothelial cell behaviour during angiogenesis - Nan, Weijin; He, Yuxi; Wang, Shurong; Zhang, Yan (Frontiers in Physiology, 2023)
Vascular endothelial (VE)-cadherin, an endothelium-specific adhesion protein, is found in the junctions between endothelial cells (ECs). It's crucial to maintain the homogeneity of ECs. Keeping and controlling the contact between ECs is essential. In addition to its adhesive function, VEcadherin plays important roles in vascular development, permeability, and tumour angiogenesis. Signal transfer, cytoskeletal reconstruction, and contractile integrating, which are crucial for constructing and maintaining monolayer integrity as well as for repair and regeneration, are the foundation of endothelial cell(EC)junctional dynamics. The molecular basis of adhesion junctions (AJs) , which are closely related and work with actin filaments, is provided by the VE-cadherincatenin complex. They can activate intracellular signals that drive ECs to react or communicate structural changes to junctions. An increasing number of molecules, including the vascular endothelial growth factor receptor 2 (VEGFR2) and vascular endothelial protein tyrosine phosphatase (VE-PTP), have been connected to VE-cadherin in addition to the conventional VE-cadherin-catenin complex. This review demonstrates significant progress in our understanding of the molecular mechanisms that affect VE-cadherin's function in the regulation of EC behaviour during angiogenesis. The knowledge of the molecular processes that control VE-cadherin's role in the regulation of EC behaviour during angiogenesis has recently advanced, as shown in this review.